Numerical Determination Of Cooling Performance On Heat Sink Using Impingement Jet - Rami Abdulraheem Abdulrezzaq Al-anı; Altuğ Karabey (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
The use of impingement jet technics drew significant attention of researchers in the recent period. In this method, significant heat transfer rates are achieved. The present study examined the cooling performance of the fin pairs, which are aligned in a consecutively enlarging-contracting pattern and have a rectangular geometry, on a heat sink. The target geometry was optimized in the previous study by using the Taguchi method. The analyses were performed using four different impingement jet velocities (10, 12, 14, and 16 m/sec.), three different nozzle diameters (D=50, 63, and 75 mm), three different heat flux values (q=2222, 3333, and 4444 W/m2), and constant nozzle-to-target distance (h/d=1) were analyzed. These results were simulated numerically by using the ANSYS Fluent software. The k-ε realizable turbulence model was selected as the best model. The numerical results showed that the mean Nusselt number is directly proportional to the increase in the Reynolds number. The Nusselt number also increased with the increasing nozzle diameter value. The results are illustrated graphically (Nu-Re) in the present study. The peak value of the local Nusselt number was found to be at the stagnation point.